2021
DOI: 10.1007/s00247-021-05081-0
|View full text |Cite
|
Sign up to set email alerts
|

European guideline for imaging in paediatric and adolescent rhabdomyosarcoma — joint statement by the European Paediatric Soft Tissue Sarcoma Study Group, the Cooperative Weichteilsarkom Studiengruppe and the Oncology Task Force of the European Society of Paediatric Radiology

Abstract: Appropriate imaging is essential in the treatment of children and adolescents with rhabdomyosarcoma. For adequate stratification and optimal individualised local treatment utilising surgery and radiotherapy, high-quality imaging is crucial. The paediatric radiologist, therefore, is an essential member of the multi-disciplinary team providing clinical care and research. This manuscript presents the European rhabdomyosarcoma imaging guideline, based on the recently developed guideline of the European Paediatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 100 publications
0
49
0
Order By: Relevance
“…The European Paediatric Soft Tissue Sarcoma Study Group (EpSSG) Imaging Committee recently developed the European RMS imaging guideline, with surveillance imaging, including magnetic resonance imaging of the primary tumor and chest radiograph for lung metastases screening, recommended every 4 months during the first 2 years offtherapy and thereafter only if new clinical symptoms develop. 18 This is a rational approach to surveillance, as the majority of relapses occur within 2 years of initial diagnosis, 19 and no studies to date have demonstrated a benefit in survival when relapse is detected by imaging. This approach reduces the overall number of imaging assessments after completion of therapy to 6, as compared with the current 12 recommended surveillance imaging time points.…”
Section: Discussionmentioning
confidence: 99%
“…The European Paediatric Soft Tissue Sarcoma Study Group (EpSSG) Imaging Committee recently developed the European RMS imaging guideline, with surveillance imaging, including magnetic resonance imaging of the primary tumor and chest radiograph for lung metastases screening, recommended every 4 months during the first 2 years offtherapy and thereafter only if new clinical symptoms develop. 18 This is a rational approach to surveillance, as the majority of relapses occur within 2 years of initial diagnosis, 19 and no studies to date have demonstrated a benefit in survival when relapse is detected by imaging. This approach reduces the overall number of imaging assessments after completion of therapy to 6, as compared with the current 12 recommended surveillance imaging time points.…”
Section: Discussionmentioning
confidence: 99%
“…[44][45][46][47] Current published data indicate that FDG avidity has a high specificity for regional lymph node involvement in RMS. [48][49][50][51][52][53][54][55][56] For example, lymph node sampling and FDG-PET-CT was performed at diagnosis in 39 patients with nonmetastatic RMS of the extremity enrolled on the European Paediatric Soft Tissue Sarcoma Group (EpSSG)-RMS2005 study, and FDG-PET-CT had a specificity of 94.4% for regional lymph node involvement. 48 ARST1431 is collecting data to further analyze the concordance between lymph node size on cross-sectional imaging, FDG avidity, and pathologic status and this may help clarify the role of FDG PET in determining N1 status.…”
Section: Evolution Of the Cog Rms-modified Tnm Staging Systemmentioning
confidence: 99%
“…Similarily, RECIST 1.1 defines abnormal lymph nodes as those ≥1.0 cm (lymph nodes ≥1.5 cm are considered both abnormal and measurable in RECIST 1.1) 44–47 . Current published data indicate that FDG avidity has a high specificity for regional lymph node involvement in RMS 48–56 . For example, lymph node sampling and FDG‐PET‐CT was performed at diagnosis in 39 patients with nonmetastatic RMS of the extremity enrolled on the European Paediatric Soft Tissue Sarcoma Group (EpSSG)‐RMS2005 study, and FDG‐PET‐CT had a specificity of 94.4% for regional lymph node involvement 48 .…”
Section: Cog Rms Modified Tnm Staging Systemmentioning
confidence: 99%
“…18 F flurodesoxyglucose positron emission tomography ( 18 F FDG PET) is not recommended in the initial staging of GCTs [73]. In pediatric and adolescent rhabdomyosarcomas, 18 F FDG PET/CT or positron emission tomography/MRI along with chest CT scan are recommended for detecting and evaluating locoregional and distant metastatic disease [74]. The chest and abdomen should be explored for malignant tumor staging and identification of metastases, the main sites being lungs and retroperitoneal lymph nodes.…”
Section: Staging Of Pediatric Testicular Tumors and Para-testicular R...mentioning
confidence: 99%